Intergroup contact in multiple adolescents’ contexts: The Intergroup Contact Interactions Scale (ICIS) - Karataş, Savaş; Rubini, Monica; Prati, Francesca; Schwartz, Seth J.; Crocetti, Elisabetta (Frontiers in Psychology, 2023)
In the present contribution, we aimed to test the psychometric properties of the Intergroup Contact Interactions Scale (ICIS). The ICIS is a tool that can easily be administered to assess ethnic minority and majority adolescents’ positive and negative intergroup contact in both school and out-of-school contexts. Study I included 169 adolescents in Italy (40.2% ethnic minority adolescents; 51.5% female; Mage=14.41) and provided initial support for the two-factor structure (i.e., positive and negative contact) of the ICIS in both school and out-of-school contexts. Study II, conducted with a sample of 1,037 adolescents in Italy (26.5% ethnic minority adolescents; 59.7% female; Mage=14.58), indicated that the fit of the two-factor ICIS structure was excellent for both school and out-of-school contexts. Measurement invariance across ethnic minority and majority adolescents was also established. We also ascertained convergent validity by highlighting meaningful associations of adolescents’ positive and negative contact with the quantity of contact as well as with their perceptions regarding parents’ positive and negative contact with outgroup members. Study III, involving a sample of 641 adolescents in Turkey (32.9% ethnic minority adolescents; 69.6% female; Mage=15.51), supported the two-factor structure, as well as convergent validity, of the ICIS in both contexts. Measurement invariance across ethnic groups was also established. Overall, these studies suggest that the ICIS is a reliable measure for studying positive and negative intergroup contact among ethnic minority and majority adolescents across school and out-of-school contexts.